P101 The long-term experience of COPD patients taught PLB: a mixed methodological study. (19th November 2012) - Roberts, SE; Schreuder, FM; Watson, T; Stern, M
Abstract : Background: Pursed lips breathing (PLB) is a breathing technique advocated for the treatment of exertional dyspnoea in COPD. Published studies to date have only reported on immediate or short-term effects. Aim: To investigate the long-term use of PLB in people with COPD trained to use this technique for dyspnoea management. Method: A purposive sample of 13 patients taught PLB 6–24 months previously were studied using semi-structured telephone interviews and a focus group. Where possible the technique of those reporting current PLB use was also observed. Results: 11 participants took part in the telephone interviews, mean age 64.6 yrs (SD11.81), mean FEV1 44.3% predicted (SD 0.19). 5/11 participated in the focus group and 6/11 were observed performing PLB. Nine reported on-going use of PLB with 8 reporting definite benefit. Four distinct themes emerged from the analysis of the data: use of PLB when short of breath due to physical activity (8/9), increased confidence and reduced panic (4/9), use as an exercise (3/9), use at night (3/9). Observed technique showed ongoing ability for PLB to reduce respiratory rate and increase oxygen saturation. Those that had discontinued PLB had done so because it didn't help (2) and they had forgotten or were too busy to continue. No substantial adverse effects were reported. Conclusion: This study investigated, for the first time, the long-term use of PLB by patients with COPD. 62% of patients studied reported benefit from PLB up to 24 months after learning the technique. The role of PLB in increasing patients' confidence in their ability to manage breathlessness and, use at night, are also novel findings.